Desain Pembelajaran Terintegrasi Mitigasi Bencana Banjir Melalui Pendekatan Science, Technology, Engineering, Mathematic And Society - Puyanti, Puyanti; Susanti, Susanti; Elza Heryenzi; Diah Suprihatin; Henny Johan (Yayasan Literasi Sains Indonesia, 2022)
The aim of the research is to design natural science learning integrated with flood disaster mitigation to equip students with an attitude of disaster preparedness. Research is a type of descriptive qualitative research. Data collection techniques through interviews and library research (library research). The results of this study, namely the natural science learning design material Global Warming which is integrated through flood disaster mitigation. The learning design uses the Science, Technology, Engineering, Mathematics and Society (STEMS) approach and the Project Based Learning (PjBL) learning model. Through the STEMS approach, students are trained to think critically, creatively, and be able to solve problems by applying science, mathematics and technology. Furthermore, with the PjBL learning model students are directed to design and design flood-free houses as a flood preparedness effort. The use of the STEMS approach and the PjBL learning model can improve students' cognitive, affective and psychomorphic abilities, to equip students with an attitude of early preparedness for disasters.